Timing of Elevations of Autoantibody Isotypes Prior to Diagnosis of Rheumatoid Arthritis. Issue 2 (26th December 2019) - Kelmenson, Lindsay B.; Wagner, Brandie D.; McNair, Bryan K.; Frazer‐Abel, Ashley; Demoruelle, M. Kristen; Bergstedt, Dylan T.; Feser, Marie L.; Moss, Laura K.; Parish, Mark C.; Mewshaw, Elizabeth A.; Mikuls, Ted R.; Edison, Jess D.; et al.
Abstract : Objective: To evaluate patterns of elevations of isotypes of rheumatoid factor (RF) and anti–citrullinated protein antibodies (ACPAs) pre–rheumatoid arthritis (RA) diagnosis and post–RA diagnosis. Methods: Using the Department of Defense Serum Repository we identified 214 RA cases and 210 matched controls. Up to 3 pre–RA diagnosis and 1 post–RA diagnosis serum samples per subject were tested for RF and for IgA, IgG, and IgM ACPAs. The timing and trajectories of elevations of autoantibodies were evaluated. Results: Autoantibody levels were elevated in cases versus controls a mean of 17.9 years before RA diagnosis for IgG ACPA, 14.2 years for IgA‐RF, 7.2 years for IgM‐RF, 6.2 years for IgA ACPA, and 5.0 years for both IgM ACPA and IgG‐RF ( P < 0.01 for all comparisons). There were similar relationships for positive or negative autoantibody status, with cases first showing positivity for IgG ACPA 1.9 years pre‐RA and for IgA‐RF 1.7 years pre‐RA, followed by the other isotypes. Only IgA ACPA positivity was significantly increased in post–RA diagnosis samples (19% 0–2 years pre‐RA versus 39% >2 years post–RA diagnosis; P = 0.04). All autoantibody levels demonstrated an early initial elevation, a period of stability, then an increase immediately before RA diagnosis. A pre‐RA endotype of early elevation of autoantibodies was associated with increased use of biologic therapy, and a higher prevalence of sicca symptoms and lung disease post–RA diagnosis. Conclusion: Differences in patterns of elevations of autoantibody isotypes have implications for understanding the pathophysiology of RA development. These include understanding what factors drive initial autoantibody elevations compared to what factors (including mucosal) drive later increases in autoantibody levels and a transition to clinically apparent RA, and how pre‐RA endotypes may influence post–RA diagnosis phenotypes.